Pengaruh Kualitas Produk, Green Marketing, dan Experiental Marketing terhadap Keputusan Pembelian (Studi Empiris pada Konsumen Kopi Lawoek Temanggung) - Aditya Hermawan; Nur Hidayah; Pranita Siska Utami (Borobudur Management Review, 2023)
This research is based on the many cases of goods and services in the market so that many products do not maintain the value of their products which results in consumer discrepancies in making purchases. The purpose of this study is to determine whether there is an influence of the Influence of Product Quality, Green Marketing and Experiential Marketing on Purchasing Decisions on Lawoek Temanggung Coffee consumers. This study used quantitative methods with a total sample of 100 people. Using Non Probability Sampling Technique by purposive sampling. Data collection techniques using questionnaires. The data analysis tools used are validity tests, reliability tests, multiple linear regression, and hypothesis tests. The results showed that product quality (X1) influenced the purchasing decision as evidenced by the t test with a significant value of 0.000<0.05. Green marketing (X2) has no effect on the purchase decision as evidenced by the t test with a significant value of 0.092>0.05. Experiential marketing affects purchasing decisions as evidenced by the t test with a significant value of 0.015<0.05.